Community-based Psychosocial Support for Orphan and Vulnerable Children living in an Orphanage - Ridhoyanti Hidayah; Endah Panca Lydia Fatma; Retno Lestari (Journal of Innovation and Applied Technology, 2023)
Orphan and children living in orphanages are a high-risk group vulnerable to psychosocial problems. Individual who lived in this community are not only orphans but also children and people from low-income families. This group could be perpetrators, witnesses and victims of bullying and other mis behaviour lead to psychosocial problems. This activity aims to improve mental health status of children and people at the Al Husna orphanage through training of early detection, prevention and early treatment for psychosocial problems through implementation of psychosocial intervention and counselling. The results are that they have experienced risk for suicide, hallucination, delusion, anxiety, and social isolation. Through the empowerment program that has been carried out by dealing with the orphan and vulnerable children, socialization and training regarding psychological well-being, early detection, prevention, and treatment could be well-implemented during their activity of daily living.